ZmNF-YB16 Overexpression Improves Drought Resistance and Yield by Enhancing Photosynthesis and the Antioxidant Capacity of Maize Plants - Wang, Baomei; Li, Zhaoxia; Ran, Qijun; Li, Peng; Peng, Zhenghua; Zhang, Juren (Frontiers in Plant Science, 2018)
ZmNF-YB16 is a basic NF-YB superfamily member and a member of a transcription factor complex composed of NF-YA, NF-YB and NF-YC in maize. ZmNF-YB16 was transformed into the inbred maize line B104 to produce homozygous overexpression lines. ZmNF-YB16 overexpression improves dehydration and drought stress resistance in maize plants during vegetative and reproductive stages by maintaining higher photosynthesis and increases the maize grain yield under normal and drought stress conditions. Based on the examination of differentially expressed genes between the wild-type (WT) and transgenic lines by quantitative real time PCR (qRT-PCR), ZmNF-YB16 overexpression increased the expression of genes encoding antioxidant enzymes, the antioxidant synthase, and molecular chaperones associated with the endoplasmic reticulum (ER) stress response, and improved protection mechanism for photosynthesis system II. Plants that overexpression ZmNF-YB16 showed a higher rate of photosynthesis and antioxidant enzyme activity, better membrane stability and lower electrolyte leakage under control and drought stress conditions. These results suggested that ZmNF-YB16 played an important role in drought resistance in maize by regulating the expression of a number of genes involved in photosynthesis, the cellular antioxidant capacity and the ER stress response.